Robot-Assisted Gait Training in Stroke Rehabilitation: A Multidisciplinary Overview on Lokomat Features - Akıncı, Murat; Akıncı, Merve; Burak, Mustafa; Erturan, Sinem; Uzun, Oznur (My University, 2025)
Stroke is a significant cause of death and disability worldwide. With the increasing lifespan, the risk of stroke has risen by 50% in the last 20 years, and currently, one in four individuals is at risk of experiencing a stroke. In the early stages of stroke rehabilitation, an interdisciplinary approach is essential to increase independence and ensure patients are discharged from the hospital in a shorter time. This approach involves physicians, physiotherapists, nurses, psychologists, and other healthcare professionals. This review examines the effects of session-specific parameters of the robot-assisted gait training device, Lokomat, used in stroke rehabilitation. Studies have shown that high guidance force levels (100%) decrease sensorimotor cortex engagement, while lower guidance force levels (30-50%) enhance muscle activation and support motor learning. Additionally, adjusting body weight support between 30% and 50% has been found to yield the most effective results. Increasing walking speed has also been observed to enhance muscle activation.
Keywords: Stroke; augmented performance feedback; body weight support